Quantity price discrimination in the air transport industry: The easyJet case. (July 2016) - Cattaneo, Mattia; Malighetti, Paolo; Morlotti, Chiara; Redondi, Renato
Abstract: This paper extends the literature on low-cost carriers' pricing strategies by investigating the presence of quantity price discrimination implemented through a two-part tariff in offered fares. By analysing Internet fares for all easyJet flights departing from the Amsterdam Schiphol airport between March and April 2015, we search for price differentials based on the number of seats booked by a single consumer. We find that the lowest average unit price is associated with a single consumer reserving 5 seats. On average, the per-seat discount for a single consumer reserving 5 seats is €9.48, which is 14% of the single-seat fare. Additionally, a multivariate analysis shows that quantity discounts are greater for flights with a larger fraction of available seats at the time of booking, the seats are booked longer in advance, and the destination's gross domestic product per capita is greater. Conversely, quantity discounts are lower for longer routes, larger destination airports, and routes for which easyJet's market share is higher. Highlights: easyJet's pricing strategy includes quantity price discrimination. The maximum quantity discount occurs when a single consumer reserves 5 seats. The 5-seat discount offered by easyJet is €9.48. Discounts vary according to both flight and route characteristics.